2011
DOI: 10.1016/j.clim.2010.12.006
|View full text |Cite
|
Sign up to set email alerts
|

B lymphocytes are resistant to death receptor 5-induced apoptosis

Abstract: Death Receptor 5 (DR5) induces apoptosis in various types of cells and is a potential therapeutic target. We have investigated whether targeting DR5 could be used to eliminate pathogenic B lymphocytes from systemic lupus erythematosus (SLE) patients. We examined DR5 expression and function on B lymphocytes from healthy controls subjects, SLE patients, and human tonsil. DR5 was expressed similarly on all B cell subpopulations, including resting and activated B cells. Expression of DR5 was equivalent on B cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…These results together suggest the potential to prevent auto-reactive B cells via modulation of the components in the inflammatory CD4-M1 pathogenic circuit. Consistent with the results we found in RA subjects [5] and previous report [32], we have analyzed peripheral blood mononuclear cells (PBMCs) from patients with SLE and have identified that treatment with TRA-8 resulted in elimination of CD4 T cells, but not CD19 B cells (Hsu et al, unpublished observations). These results suggested that consistent with results obtained from mice and human RA, CD4 T cells, but not B cells from SLE patients could be depleted by TRA-8 therapy.…”
Section: Introductionsupporting
confidence: 87%
“…These results together suggest the potential to prevent auto-reactive B cells via modulation of the components in the inflammatory CD4-M1 pathogenic circuit. Consistent with the results we found in RA subjects [5] and previous report [32], we have analyzed peripheral blood mononuclear cells (PBMCs) from patients with SLE and have identified that treatment with TRA-8 resulted in elimination of CD4 T cells, but not CD19 B cells (Hsu et al, unpublished observations). These results suggested that consistent with results obtained from mice and human RA, CD4 T cells, but not B cells from SLE patients could be depleted by TRA-8 therapy.…”
Section: Introductionsupporting
confidence: 87%
“…In humans, TRAIL expression was described on various different innate and adaptive immune cell types including monocytes, macrophages, natural killer (NK) cells, T cells and B cells (2326). TRAIL-R expression has been described in central and peripheral T cells and naïve and memory B cells upon activation (27, 28). While several non-transformed human cell types express TRAIL-Rs, many are refractory to the pro-apoptotic function of the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been shown that non-transformed cells can be sensitized to TRAIL-induced apoptosis by activating cues or viral infections (2931). However, the results were depending on activation protocols and specific cellular subsets, leading to inconsistent conclusions (27, 28, 32, 33). A systematic description of TRAIL-Rs in human B cell subpopulations is missing, as well as a comprehensive analysis of the sensitivity of primary human B cells to TRAIL-induced apoptosis ex vivo and upon activation.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of TRAIL on human B cells was seen with IFNα and IFNα-inducers, like TLR9 ligands [51], but not following stimulation via the BCR, PHA/IL-2, or IFNβ [51,53]. Furthermore, naïve B cells expressed DR4 [27,239,240] and DR5 [32,239,240,241] and their expression levels increased upon stimulation [239,240,242]. Consequently, germinal center (GC) or memory B cells expressed higher levels of DR4 and DR5 than naïve cells [239,240].…”
Section: Expression and Function Of Trail/drs In Immune Cellsmentioning
confidence: 99%